AWESOME NIGHT: REFLECTING ON MEMORIES OF USM ALUMNI - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KUALA LUMPUR, 14 October 2016 – The Minden campus of Universiti Sains Malaysia (USM) 45 years ago has etched many stories of its own, with some would fade as the days passed while others would remain amidst the varied individuals and the closeness between one another and with the surroundings.